2013
DOI: 10.1152/ajpcell.00227.2013
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for paracrine/autocrine regulation of GLP-1-producing cells

Abstract: Glucagon-like peptide-1 (GLP-1), secreted from gut L cells upon nutrient intake, forms the basis for novel drugs against type 2 diabetes (T2D). Secretion of GLP-1 has been suggested to be impaired in T2D and in conditions associated with hyperlipidemia and insulin resistance. Further, recent studies support lipotoxicity of GLP-1-producing cells in vitro. However, little is known about the regulation of L-cell viability/function, the effects of insulin signaling, or the potential effects of stable GLP-1 analogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 36 publications
(40 reference statements)
0
23
0
Order By: Relevance
“…Tatarkiewicz et al [47] suggested the existence of an additional novel receptor signaling pathway complementing the actions of Ex-4. Kappe et al [48] found the cross talk between tyrosine kinase receptors (e.g., the insulin receptor) and GLP-1R and that Ex-4 may exert an effect on tyrosine kinase receptors, which transmit signals to activate downstream pathways of GLP-1R. However, the exact mechanism of how Ex-4 enters into ADMSCs and subsequently activates signal pathways needs more research.…”
Section: Discussionmentioning
confidence: 99%
“…Tatarkiewicz et al [47] suggested the existence of an additional novel receptor signaling pathway complementing the actions of Ex-4. Kappe et al [48] found the cross talk between tyrosine kinase receptors (e.g., the insulin receptor) and GLP-1R and that Ex-4 may exert an effect on tyrosine kinase receptors, which transmit signals to activate downstream pathways of GLP-1R. However, the exact mechanism of how Ex-4 enters into ADMSCs and subsequently activates signal pathways needs more research.…”
Section: Discussionmentioning
confidence: 99%
“…the insulin-producing β-cells [120]. Such autocrine feedback may be operative also in GLP-1-secreting cells, where GLP-1R expression on L-cells and its involvement in GLP-1 secretion has previously been suggested by data from in vivo and in vitro studies [77,121]. Although a recent study indicated that GLP-1 and its degradation products do not modulate L-cell basal secretion of GLP-1(7-36) amide, any potential feedback mechanisms acting on post prandial responses were not investigated [122].…”
Section: Neuroendocrine Signalsmentioning
confidence: 93%
“…Whether intestinal L-cells express the GLP-1R, which would facilitate autocrine signalling by the peptide, is still debated. Some studies indicate the presence of the GLP-1R in GLP-1 producing cells [77,121], where the GLP-1R has been demonstrated with immunocytochemistry, and GLP-1R mRNA expression has been reported in GLP-1-producing GLUTag cells [121]. However, other studies have failed to detect any GLP-1R expression in GLP-1-producing cells [50].…”
Section: Hormonal and Nutritional Control Of L-cell Differentiationmentioning
confidence: 99%
See 2 more Smart Citations